Acceptance factors of telemedicine in times of COVID-19: Case Argentina - Schlottke, Jorge Anibal (2024)
We performed an analytical, cross-sectional study of 285 consumers to assess the influence of social influence, resistance to use, facilitators to use, perceived ease of use and perceived usefulness of telemedicine on the intention to use telemedicine of citizens of Argentina in times of the pandemic by COVID-19. The proposed research model was analyzed using partial least square structural equation modeling (PLS-SEM). Perceived ease of use had a positive effect (0.624) on perceived usefulness; facilitating conditions had a positive effect (0.476) on usage intention; perceived risk (-0.062) and social influence (0.072) did not have an effect on usage intention. Bootstrapping showed that the beta coefficients were statistically significant. The outcomes may provide ideas to healthcare managers to know what an expectation about telemedicine is and develop new services directed to patients. Copyright Schlottke JA et al. This is an open access article distributed under the terms of the Creative Commons Attribution License (CC-BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.